Abnormalities in Serum Electrolytes in DF, DHF and DSS as Prognostic Indicators for Dengue Severity: A Comparative Model - Wali Ur Rehman, Shah Zeb, Sidra Noureen, Sofia Razzaq Meo, Ahsan Naeem, Fahim Ullah, Syed Sohail Ahmed, Assad Rehman, Sana Jalal, Tufail Muhammad, Hilal Ahmad, Adnan Hussain Tanoli, Jawad Ullah, Imranullah Rahimi, Nasirullah Adil (Pakistan Journal of Medical & Health Sciences, 2022)
About 250 positive patients were included in the study for diagnosis, of whom 146 were Male and 104 were Female. The M±SD of severity level in DF and DHF patients was 120.5±53.3, Variance=2841.18, Cl95% 1.960, and P=value was calculated as 0.001. The Comparative Analysis of DF and DHF symptoms between group SS (576), df (1), MS (576), F (0.52978) and p=value was calculated p=.478. Whereas within groups SS (15221.5), df (14), MS (1087.25), F (0.52978) and p=value was calculated as p=.478. The M±SD of severity level in DF and DSS patients was 118.4±59.5, Variance=3551.96, Cl95% 1.960, and P=value was calculated as 0.001. The M±SD of dengue serological markers such as 20±9.26, Variance=85.824, and Cl95% 1.960. The M±SD of Na+ in DF 132.4±3.8, DHF 129.5±2.5, DSS 119.5±2.5. K+ in DF 3.38±0.32, DHF 2.97±1.01, DSS 2.4±0.93. Ca+ in DF 8.81±0.53, DHF 7.82±1.2, DSS 6.36±0.57. Mg+ in DF 1.39±0.71, DHF 1.39±0.41, DSS 1.62±0.31. Po4 in DF 3.47±0.53, DHF 2.21±0.62, and DSS 2.34±0.31. It was concluded that dengue shock syndrome patients were found highly affected by serum electrolytes, so we need to focus on the replacement and treatment of serum electrolytes. Keywords: Dengue virus, Civil Hospital, Serological Markers, Abnormal Serum Electrolytes, Clinical manifestation